CHINA IN CENTRAL EURASIA: SECURITY INTERESTS AND GEOPOLITICAL ACTIVITY - EYVAZOV, Jannatkhan (CENTRAL ASIA AND THE CAUCASUS, 2010)
Today, extended geographical links are the most important yet far from the only factor that makes Central Eurasia1 highly significant for China’s conceptualization of its security. The Soviet Union’s disintegration, which created newly independent states, also generated favorable conditions for China’s progress toward the superpower status. At the same time, Central Eurasia, or rather the advent of anarchy across its political space and the rising ethnoterritorial problems which might well affect China’s northwestern regions, called for fresh approaches to the area. By the same token, its geopolitical importance for China’s relations with its main rivals at the supra-regional level was exacerbated. In these conditions, China should become more actively involved in the Central Eurasian space freed from Soviet domination, which means that it should join the current rivalry for geopolitical control over the vast area. In this article I want to look at the security interests which form the cornerstone of Chinese policy in Central Eurasia, identify the geopolitical importance of this area for China, and trace the tactical specifics of China’s regional policies.